2019
DOI: 10.4103/ijpc.ijpc_57_19
|View full text |Cite
|
Sign up to set email alerts
|

Emergency department visits by head-and-neck cancer patients

Abstract: Aim:This study was conducted to assess the disease status of head-and-neck cancer patients visiting the emergency department (ED) and their reason for presentation. We wanted to analyze if these visits could be avoided by incorporating any changes in our clinical practice.Methods:This was a retrospective analysis of head-and-neck cancer patients attending the ED at a tertiary care cancer center in 2017. Clinical details were noted from the electronic medical records, and descriptive statistics was calculated. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 9 publications
(18 reference statements)
1
8
1
Order By: Relevance
“…These findings are consistent with the rates reported in previous studies for HNC, 13,26 and indicate the significant clinical burden of cancer on patients and the healthcare system. In terms of hospital admission following ED visits, a study 27 reported 43% inpatient admission for oral cancer patients, which is comparable to our results; however, other studies reported a wide range of hospital admission rates 28–30 . The observed variations could be due to regional differences in management strategies, cancer stage, and treatment methods.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…These findings are consistent with the rates reported in previous studies for HNC, 13,26 and indicate the significant clinical burden of cancer on patients and the healthcare system. In terms of hospital admission following ED visits, a study 27 reported 43% inpatient admission for oral cancer patients, which is comparable to our results; however, other studies reported a wide range of hospital admission rates 28–30 . The observed variations could be due to regional differences in management strategies, cancer stage, and treatment methods.…”
Section: Discussionsupporting
confidence: 85%
“…Moreover, postoperative infection was observed as a frequent reason for ED visits, which is a common condition for oral oncological surgeries 37 . The observed symptoms in this study; however, were different from some studies that reported pain, respiratory distress, fatigue, and weakness as the chief complaints 29,30 . These studies investigated HNC patients and the discrepancy may be due to the differences in the types of cancers prevalent in different populations and therefore differences in treatment modalities.…”
Section: Discussioncontrasting
confidence: 74%
“…Thirty-nine studies reported disease-related factors . 7 , 11 , 14 , 29-37 , 39 , 41 , 43-47 , 49-68 Three disease-site predictors were significant ( Table 2 ). Lung cancer is a primary site highly associated with ED visits, ranging from 7% to 64.9%, with 3-fold higher odds (compared with hematological cancers) of visiting the ED.…”
Section: Resultsmentioning
confidence: 99%
“…Despite the availability of the World Health Organization's (WHO) "analgesic ladder" guideline designed for pain relief [9][10][11], managing pain, particularly in patients undergoing RT for head and neck cancers (HNC), remains a significant challenge for healthcare providers, with nearly onethird of HNC patients continuing to experience severe, uncontrolled pain [12][13][14]. The challenge in the control of RT-induced acute pain is potentially related to the complex nature of pain, the multifactorial etiology of pain and the different response rates of individuals to pain treatment [5,15].…”
Section: Introductionmentioning
confidence: 99%